Transcriptome landscape comparison of periodontium in developmental and renewal stages - Deng, Yuwei; Luo, Nan; Xie, Ming; He, Ling; Jiang, Ruixue; Hu, Nan; Wen, Jin; Jiang, Xinquan (Frontiers in Endocrinology, 2023)
Objectives: Periodontium regeneration remains a significant challenge in clinics and research, and it is essential to understand the stage-specific biological process in situ. However, differing findings have been reported, and the mechanism has yet to be elucidated. The periodontium of adult mice molars is considered to be stable remodeling tissue. At the same time, the continuously growing incisors and the developing dental follicle (DF) of postnatal mice highly represent fast remodeling tissue. In this study, we attempted to explore different clues of temporal and spatial comparisons to provide improved references for periodontal regeneration. Methods: Periodontal tissues from the developing periodontium (DeP) of postnatal mice, and continuously growing periodontium (CgP) and stable remodeling periodontium (ReP) of adult mice were isolated and compared using RNA sequencing. Based on the Dep and CgP separately compared with the ReP, differentially expressed genes and signaling pathways were analyzed using GO, KEGG databases, and Ingenuity Pathway Analysis (IPA). The results and validation were obtained by immunofluorescence staining and RT-PCR assays. Data were expressed as means ± standard deviation (SD) and analyzed by GraphPad Prism 8 software package, and one-way ANOVA was used to test multiple groups. Results: Principal component analysis showed that the three groups of periodontal tissue were successfully isolated and had distinct expression profiles. A total of 792 and 612 DEGs were identified in the DeP and CgP groups compared with the ReP. Upregulated DEGs in the DeP were closely related to developmental processes, while the CgP showed significantly enhanced cellular energy metabolism. The DeP and CgP showed a common downregulation of the immune response, with activation, migration, and recruitment of immune cells. IPA and further validation jointly suggested that the MyD88/p38 MAPK pathway played an essential regulatory role in periodontium remodeling. Conclusion: Tissue development, energy metabolism, and immune response were critical regulatory processes during periodontal remodeling. Developmental and adult stages of periodontal remodeling showed different expression patterns. These results contribute to a deeper understanding of periodontal development and remodeling and may provide references for periodontal regeneration.